Entry and the accumulation of capital: A two state-variable extension to the Ramsey model - Paulo Brito; Huw Dixon (Cardiff University, Cardiff Business School, 2007)
In this paper we consider the entry and exit of Örms in a dynamic general equilibrium model with capital. At the Örm level, there is a Öxed cost combined with increasing marginal cost, which gives a standard U-shaped cost curve with optimal Örm size. Entry is determined by a free entry condition such that the costs of entry are equal to the present value of incumbent Örms, the cost of entry (exit) depends on the áow of entry (exit). Then equilibrium is saddlepoint stable and the stable manifold is two-dimensional. Transitional dynamics can, under certain circumstances, be non-monotonic.
Keywords: D92; C62; E32; O41; 330; Entry; dynamics; Ramsey; Markteintritt; Kosten; Dynamisches Gleichgewicht